The impact of international achievement studies on national education policymaking - Wiseman, Alexander W., 1968- (Bingley, U.K. : Emerald, 2010)
Since the IEAs first international studies on mathematics and science achievement in the late 1960s, the availability and use of international achievement studies around the world has exploded. The most widely adopted studies, PISA and TIMSS, are now administered regularly and include participating countries from every region around the world. These international studies, now include cross-national studies of multiple subject areas, teachers and teaching, and a developing focus on higher education. This information has been used to make decisions about resource distribution both within and across national educational systems, but some of the most productive uses of TIMSS and PISA data by policymakers have been to create agendas for innovation and equity in national educational systems. The chapters in this volume will (1) discuss the uses of international achievement study results as a tool for national progress as well as an obstacle, (2) provide recommendations for ways that international achievement data can be used in real-world policymaking situations, and (3) discuss what the future of international achievement studies holds.
Introduction : the advantages and disadvantages of national education policymaking informed by international achievement studies / Alexander W. Wiseman -- Monitoring the quality of education : exploration of concept, methodology, and the link between research and policy / Mioko Saito, Frank van Cappelle -- Why participate? Cross-national assessments and foreign aid to education / Rie Kijima -- Does inequality influence the impact of schools on student mathematics achievement? A comparison of nine high-, medium-, and low-inequality countries / Amita Chudgar, Thomas F. Luschei -- New directions in national education policymaking : student career plans in international achievement studies / Joanna Sikora, Lawrence J. Saha -- Analyzing Turkey's data from TIMSS 2007 to investigate regional disparities in eighth grade science achievement / Ebru Erberber -- The impact of standardized testing on education quality in Kyrgyzstan : the case of the Program for International Student Assessment (PISA) 2006 / Duishon Shamatov, Keneshbek Sainazarov -- From equity of access to international quality standards for curbing corruption in secondary and higher education and closing achievement gaps in post-Soviet countries / Mariam Orkodashvili -- A comparative analysis of discourses on equity in education in the OECD and Norway / Cecilie Rønning Haugen -- The impact of international achievement studies on national education policymaking : the case of Slovenia : how many watches do we need? / Eva Klemencic -- Finland, PISA, and the implications of international achievement studies on education policy / Jennifer H. Chung -- Why the fireworks? : theoretical perspectives on the explosion in international assessments / Jennifer DeBoer -- Standardized tests in an era of international competition and accountability / M. Fernanda Pineda.
Print version record
Keywords: Education -- General; Education -- Comparative; Educational strategies & policy; Organization & management of education; Educational statistics; Educational planning -- Statistical methods